2020
DOI: 10.1002/jmv.26282
|View full text |Cite
|
Sign up to set email alerts
|

Acute HIV infection in a large teaching hospital in western China: Clinical, virological, and molecular epidemiological characteristics

Abstract: Objective To provide information on clinical, virological, and molecular epidemiological characteristics for early identification, diagnosis, and treatment of acute HIV infection (AHI). Methods A retrospective study was conducted with patients with AHI from 2012 to 2017 in West China Hospital. Results A total of 47 patients with AHI were found using a fourth‐generation kit. Thirteen (27.66%) of these patients were negative if tested by third‐generation tests. Median age of patients with AHI was 26 and 91.49% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
1
1
Order By: Relevance
“…TDR is another determinant that may impact the achievement of the last 95% target. Intriguingly, extremely high rates of TDR were found in this study, which were substantially higher than those in previous reports [5,37] . Previous studies showed a wide range (2.0%–15.0%) [38,39] of prevalence of TDR in China and significantly higher levels in developed countries (8.3%–17.2%), [40–44] which differs according to the study population, time interval, and definition of TDR.…”
Section: Discussioncontrasting
confidence: 83%
See 1 more Smart Citation
“…TDR is another determinant that may impact the achievement of the last 95% target. Intriguingly, extremely high rates of TDR were found in this study, which were substantially higher than those in previous reports [5,37] . Previous studies showed a wide range (2.0%–15.0%) [38,39] of prevalence of TDR in China and significantly higher levels in developed countries (8.3%–17.2%), [40–44] which differs according to the study population, time interval, and definition of TDR.…”
Section: Discussioncontrasting
confidence: 83%
“…Intriguingly, extremely high rates of TDR were found in this study, which were substantially higher than those in previous reports. [ 5 , 37 ] Previous studies showed a wide range (2.0%–15.0%) [ 38 , 39 ] of prevalence of TDR in China and significantly higher levels in developed countries (8.3%–17.2%), [ 40 44 ] which differs according to the study population, time interval, and definition of TDR. The high prevalence of drug resistance against NNRTI would pose a great threat to NNRTI-containing regimens in resource-limited regions in future.…”
Section: Discussionmentioning
confidence: 99%